Experimental and Statistical Investigation of Hydrodynamics of a Falling Liquid Film - ambros, christoph (My University, 2015)
In falling film evaporators a liquid flows down a heated surface as a thin film under gravity. They can be operated at very low pressures and are thus convenient for the evaporation of viscous and temperature sensitive liquids. Falling liquid films are random in nature and the film response is stochastic. The hydrodynamics haven´t been fully understood so far. Therefore the liquid flow pattern are described by statistical analysis. The flow pattern are investigated at four positions on the outside of a vertical pipe with five meter in length. The dependence on the Reynolds number and viscosity is studied at single positions as well as longitudinal. The experiments are done under non-evaporating- and ambient conditions. The instantaneous film thickness measurements are done by a new laser measurement approach, measuring with a frequency of 500 Hz. A selection of the most promising parameters and statistical methods to describe the liquid flow pattern are determined. A new method has been developed to distinguish between waves with different amplitudes. The results of the liquid flow pattern by using the new measurement approach results in highly resolved film thickness traces. The new method to distinguish between the waves, gives very pronounced points of transition between different flow regimes. The transitions from the capillary-wavy-laminar into the inertia-wavy-laminar, from the inertia-wavy-laminar into the inertia-wavy-turbulent as well as the transition into fully turbulent flow have been investigated. The results of the critical Reynold numbers, marking the transitions between the flow regimes show a high dependency on the position at the pipe as well as viscosity. The work makes a valuable contribution to understand the hydrodynamics of a falling liquid film by investigating the liquid flow pattern.
Keywords: Energi; Hållbar utveckling; Annan kemiteknik; Energy; Sustainable Development; Other Chemical Engineering